Determination of Sulfide and Total Sulfur in Ore by Wavelength-Dispersive X-ray Fluorescence. (1st September 2016) - Chubarov, Victor; Aisueva, Tatiana; Finkelshtein, Alexander
ABSTRACT: This paper describes the determination of total sulfur and sulfide in ore by X-ray fluorescence. The X-ray emission spectra of sulfur were measured by a wavelength-dispersive spectrometer. The samples were prepared as pressed powder pellets on boric acid substrates. The SKα1, 2 line was used to determine total sulfur. The ratio between sulfide and total sulfur was measured by the ratio of satellite SKβ′ and SKβ1, 3 line intensities. The total relative standard deviation (SD) of the measurements and preparation repeatability was less than 2%. Sample preparation was contributed to the error of the analysis. To determine total sulfur, the calibration curve was obtained from the samples of certified reference materials of gold-bearing sulfide-containing ore. The accuracy was verified by comparison with a gravimetric method. The relative SD was 6% for sulfur concentrations from 1 to 8 wt%. The calibration curve was defined using pure reagents to determine sulfide. The ore was analyzed by a gravimetric procedure with a relative SD of 6.5% for the sulfide concentration from 1 to 6 wt%.